Celebrity worship and body image satisfaction: An analytical research among adolescents in Tangerang Indonesia - Azizah, Shieva Nur; Kristiutami, Apriyati (Universitas Aisyah Pringsewu, 2020)
The activities of the Idol are many found in teenagers, as a form of self-seeking. The youth can adore it to emulate his idol, so as to desire like someone in his idol. Research objectives to find out if there is an idol-like behavior relationship with the satisfaction of body image in adolescents. This type of research using a cross-sectional research method with a sample of 126 respondents. Sampling techniques using purposive sampling. The results of this study used the Chi-Square statistical test. The results of this study showed that respondents who experienced the behavior of imitating as much (50.8 percent) And who experienced the worshipping behavior (49.2 percent), while respondents who had dissatisfied body image (58.7 percent) and satisfying body image (49.3 percent). The results of a statistical test of Chi-Square p-value 0.001 (p less than 0.05) so that there is a behavioral relationship with body image satisfaction in teenager vocational high school in Tangerang. It is hoped that the study of teenagers who have idols can control the behavior of the idol to increase the satisfaction of his body image to be positive.Perilaku mengidolakan dan kepuasan citra tubuh: Riset analitik pada remaja di TangerangAbstrak: Kegiatan pengidolaan banyak ditemukan pada remaja, sebagai bentuk pencarian jati diri. Remaja dapat memuja hingga meniru idolanya, sehingga berkeinginan seperti seseorang diidolanya. Tujuan penelitian untuk mengetahui apakah ada hubungan perilaku seperti idola dengan kepuasan citra tubuh pada remaja. Jenis penelitian ini menggunakan metode penelitian cross sectional dengan sampel 126 responden. Teknik pengambilan sampel menggunakan purposive sampling. Hasil penelitian ini menggunakan uji statistik Chi Square. Hasil penelitian ini menunjukkan bahwa responden yang mengalami perilaku meniru sebanyak (50,8 persen) dan yang mengalami perilaku memuja (49,2 persen), sedangkan responden yang memiliki citra tubuh tidak puas (58,7 persen) dan citra tubuh puas (49,3 persen). Hasil uji statistik Chi Square p-value sebesar 0,001 (p kurang dari 0,05) sehingga ada hubungan perilaku dengan kepuasan citra tubuh pada remaja SMK di Tangerang. Diharapkan dengan penelitian ini remaja yang memiliki idola dapat mengontrol perilaku mengidolakan agar meningkatkan kepuasan citra tubuhnya menjadi positif.